Effects of Creep Feed Provision on Behavior and Performance of Piglets Around Weaning - Middelkoop, Anouschka; Choudhury, Raka; Gerrits, Walter J. J.; Kemp, Bas; Kleerebezem, Michiel; Bolhuis, J. Elizabeth (Frontiers in Veterinary Science, 2020)
Creep feed provision may ease weaning, hence we determined the impact of providing fibrous creep feed before weaning and adding this feed to the post-weaning diet on piglet behavior and performance. Pre-weaning, litters with on average 12 piglets were given creep feed (CF, n = 12 litters) or not (NF, n = 10 litters). Post-weaning, piglets (n = 8 pens with 4 piglets/treatment) were given a weaner diet (CON) or weaner diet supplemented with creep feed (CS). Behaviors were scored in the home pen at d11, 16, 22 and 27 after birth and at wk 1 and 2 post-weaning. Feed intake, growth and fecal consistency were measured up to d14 post-weaning. A blood sample was taken at d2, 15 and 29 after birth and d2, 5 and 14 post-weaning. CF-piglets consumed on average 397 ± 71 g creep feed before weaning. CF-piglets grew faster in the last week before weaning than NF-piglets (249 ± 7 vs. 236 ± 11 g/d, F(1,18) = 5.81, P = 0.03). However, CF- and NF-piglets did not differ in weaning weight, within-litter coefficient of variation in weaning weight, behaviors in the farrowing and weaner pen, and haptoglobin concentrations. Creep feed supplementation enhanced feed exploration at wk 2 post-weaning (0.29 ± 0.08 vs. 0.11 ± 0.03%, F(1,27) = 5.27, P = 0.03), but did not affect other post-weaning behaviors. Pre-weaning creep feed provision and post-weaning creep feed supplementation did not affect overall feed intake, growth, feed efficiency and fecal consistency for the first 14 days post-weaning, neither body weight at d14 post-weaning. Nevertheless, CF-piglets had a lower within-pen coefficient of variation in body weight at d14 post-weaning than NF-piglets (13.6 ± 1.9 vs. 15.1 ± 1.5%, F(1,26) = 6.89, P = 0.01). In conclusion, pre-weaning creep feed provision and post-weaning creep feed supplementation had no clear effects on piglet behavior and performance.